An unusual cause of myocardial ischemia: Compression of a left internal mammary artery grafting to the left anterior descending artery by a pacemaker lead. Issue 3 (September 2017) - Corré, Jérôme; Chassaing, Stephan; Arnould, Marc-Antoine; Barbey, Christophe; Bar, Olivier; Blanchard, Didier
Abstract: An 83-year-old patient, with prior history of coronary artery disease treated by coronary-artery bypass graft with left internal mammary artery (LIMA) to the left anterior descending artery (2001) and angioplasty of the right coronary artery (2012) and prior pacemaker through left subclavian vein (2014), was referred to coronary angiography for an anterior silent ischemia. It found no evolving lesion on the native coronary artery network (compared with 2012 review) but revealed an external compression of the LIMA bridge by the pacemaker lead. Conservative treatment was chosen rather than explantation and reimplantation of stimulus material or LIMA angioplasty. <Learning objective: This case highlights the interest for preferential use of the cephalic pathway in patients with left internal mammary bypass graft undergoing cardiac pacing.>